Secondary School Teachers' Self-Efficacy Levels: Elazig Province Sample - Gökyer, Necmi; Bakcak, Serkan (Fırat University, 2018)
The purpose of this research is to determine the self-efficacy levels of secondary school teachers. This research is in the instant scanning model. The universe of the research constitutes a total of 1602 teachers working in middle schools in the center of Elazığ and the districts in the academic year of 2017-2018. The sample forms a total of 360 teachers determined by simple random sampling. “Teachers' Sense of Efficacy Scale" developed by Tschannen-Moran and Hoy (2001) and adapted to Turkish by Çapa, Çakıroğlu and Sarıkaya (2005) was used as the data collection tool in the research. Professional self-efficacy levels of the branch teachers participating in the research are sufficient in all sub-dimensions and in the whole scale. According to the gender variable, the sub-dimensions of self-efficacy for classroom management and selfefficacy for teaching strategies and in the whole scale, self-efficacy levels of male teachers are higher than female teachers. It was determined that self-efficacy levels of teachers who work in schools with a small number of students are lower than those who work in schools with a high number of students. There is no significant difference between the self-efficacy levels of the branch teachers according to the variables such as seniority, branch, place of work, duration at the school and education level.

Bu araştırmanın amacı, ortaokul öğretmenlerinin özyeterlik düzeylerini belirlemektir. Bu araştırma anlık tarama modelindedir. Araştırmanın evrenini, Araştırmanın evrenini, 2017-2018 eğitim öğretim yılında, Elazığ merkez ve ilçelerin merkezindeki ortaokullarda görev yapan toplam 1602; Örneklemini ise, basit tesadüfi örnekleme yolu ile belirlenen toplam 360 öğretmen oluşturmaktadır. Araştırmada veri toplama aracı olarak, Orijinali Tschannen-Moran ve Hoy (2001) tarafından geliştirilen  ve Çapa, Çakıroğlu, Sarıkaya (2005) tarafından Türkçe’ye uyarlanan “Teachers’ Sense of Efficacy Scale” (Öğretmen Öz-Yeterlik Ölçeği) kullanılmıştır. Araştırmaya katılan branş öğretmenlerinin bütün alt boyutlarda ve ölçeğin tamamında mesleki öz yeterlik düzeyleri oldukça yeterlidir. Cinsiyet değişkenine göre, sınıf yönetimine yönelik özyeterlik, öğretim stratejilerine yönelik özyeterlik alt boyutlarında ve ölçeğin tamamında erkek öğretmenlerin özyeterlik düzeyleri kadın öğretmenlere göre daha yüksektir. Öğrenci sayısı az olan okullarda görev yapan öğretmenlerin özyeterlik düzeylerinin, öğrenci sayısı yüksek olan okullarda görev yapanlara göre daha düşük olduğu saptanmıştır. Kıdem, branş, çalıştıkları yerleşim yeri, okuldaki görev süresi ve eğitim düzeyi değişkenlerine göre, branş öğretmenlerinin özyeterlik düzeyleri arasında anlamlı bir fark çıkmamıştır.
Ortaokul Öğretmenlerinin Özyeterlik Düzeyleri: Elazığ İli Örneği